Bibliometric analysis of logistics and supply chain research (2020–2024) - Mahmoud Khalifa (International Business Logistics Journal)
Purposes This study presents a comprehensive bibliometric analysis of logistics and supply chain management (LSCM) research published between 2020 and 2024, addressing the central research question: What are the trends, key research themes, and leading contributors in LSCM scholarship during this period? The study has three main purposes: a) providing an overview of research outputs in logistics and supply chain, b) analyzing author, institutional, and country-level productivity and impact using bibliometric indicators, and c) addressing the most impactful journals, publications, and funding bodies contributing to the field. Methodology The study employed the bibliometric analysis approach to ensure an in-depth analysis for research development. Drawing on metadata from the OpenAlex scholarly database, 63,095 publications were analyzed to identify the most influential authors, institutions, journals, and funding bodies, as well as thematic and geographic patterns in the literature. The analysis employed structured search strategies, citation metrics, and Field-Weighted Citation Impact (FWCI) scores, supported by tools such as the OpenAlex API and Microsoft Excel for data extraction, visualization, and analysis. Results The findings reveal a significant increase in research output, with 77.6% of the publications being peer-reviewed journal articles and 53.2% available through open access. English was the dominant language (90.9%), and China led in publication volume (19.8%), followed by the United States and India. The most prolific author by publication count was Biswajit Sarkar, while Dmitry Ivanov ranked highest in both total citations and FWCI. The Journal of Cleaner Production emerged as the top source in terms of both volume and academic impact. Key research themes included digital transformation, Industry 4.0 technologies, sustainability, supply chain resilience, risk management, and blockchain applications. Despite strong national contributions, particularly from Asian countries, the study identified limited cross-institutional collaboration as a persistent gap. Overall, the analysis provides a data-driven overview of the evolving priorities, scholarly influence, and global participation in LSCM research over the past five years.   Received on: 11 April 2025 Accepted on: 06 June 2025 Published on: 29 June 2025